Plant pathogenic nematode exosomes remodel vector tracheae to enhance pathogen transmission - Yue Chang; Jiao Zhou; Fangyuan Ye; Hongxia Zhang; Jianghua Sun; Lilin Zhao (Proceedings of the National Academy of Sciences, 2026)
Pathogens frequently employ vector-manipulation strategies to enhance their transmission efficiency. Exosomes are increasingly recognized as mediators of interspecific communication between pathogens and their vectors. However, the mechanisms by which plant pathogenic nematode exosomes mediate cross-kingdom manipulation of vector development remain largely unexplored. Here, we demonstrate that the plant pathogenic nematode ( Bursaphelenchus xylophilus ), transmitted by the vector beetle ( Monochamus alternatus ), secretes exosomes containing microRNAs (miRNAs) that remodel the tracheal development of its vector. Upon nematode entry into the trachea, the beetle’s tracheal diameter was markedly enlarged. Notably, exosome-like vesicles released from dispersal nematodes were internalized by the tracheal epithelial cells. Moreover, exosome-derived Bx-miR-71-5p directly activates Notch expression, a key regulator of cell proliferation and differentiation. Notch suppresses the expression of matrix metalloproteinases 3 ( Mmp3 ), a critical enzyme for extracellular matrix (ECM) degradation, thereby promoting continuous ECM accumulation. Nanomaterial-mediated delivery of Bx-miR-71-5p to the vector beetle trachea upregulates the Notch gene, leading to significant increases in ECM thickness and tracheal diameter, which consequently enhances nematode load. Collectively, this study identifies nematode exosomes as the delivery vehicle for Bx-miR-71-5p and defines a Notch–Mmp3–ECM axis through which pathogen signals remodel tracheal architecture to enhance vector competence and nematode load. These findings highlight that exosomes-mediated miRNA delivery may present a conserved “toolkit” that can tune vector traits, and ultimately facilitates pathogen transmission efficiency during invasion.